Nasal Breathing Disorders in Children and Current Ways of Its Treatment - S.M. Pukhlik (Zdorovʹe Rebenka, 2012)
The paper deals with the features of rhinitis clinical course and current ways of its treatment. The results of Mili Nosik application in children with rhinosinusitis have been considered.